2020
DOI: 10.31851/jmksp.v5i2.3833
|View full text |Cite
|
Sign up to set email alerts
|

Implementasi Supervisi Akademik Dalam Meningkatkan Kinerja Guru

Abstract: Penelitian ini bertujuan untuk mengetahui bagaimana kinerja guru Sekolah Dasar dapat ditingkatkan melalui supervisi akademik yang dilakukan oleh kepala Sekolah Dasar. Penelitian ini dilaksanakan di SD Negeri 16 Gelumbang. Metode penelitian yang di gunakan adalah metode kualitatif dengan pendekatan deskriptif. Alat pengumpul data menggunakan wawancara, observasi, dokumentasi dan kajian pustaka. Hasil penelitian menyatakan bahwa proses supervisi akademik dilaksanakan oleh kepala sekolah melalui beberapa tahapan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0
14

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 0 publications
4
16
0
14
Order By: Relevance
“…This study is in line with research by (Zulfakar et al, 2020;Nurhidayanti et al, 2021;Suharto, 2018) in research on the consequence of academic supervision and teacher performance. It was found that academic supervision had a significant positive effect on teacher performance.…”
Section: Table 1 Multiple Regression Test Resultssupporting
confidence: 92%
“…This study is in line with research by (Zulfakar et al, 2020;Nurhidayanti et al, 2021;Suharto, 2018) in research on the consequence of academic supervision and teacher performance. It was found that academic supervision had a significant positive effect on teacher performance.…”
Section: Table 1 Multiple Regression Test Resultssupporting
confidence: 92%
“…Dengan demikian dapat dikemukakan bahwa hasil supervisi akademik dapat meningkatkan kinerja guru di SD Negeri 16 Gelumbang (Zulfakar & Fitria, 2020). Hal ini menunjukkan bahwa kegiatan supervisi akademik yang dilakukan oleh Kepala Sekolah sangat penting karena berpengaruh terhadap peningkatan kompetensi guru khususnya kompetensi pedagogik.…”
Section: Pendahuluanunclassified
“…One of the goals of academic supervision is to provide technical assistance and guidance to teachers so that they can achieve their best performance [13]. Similarly, Zulfakar [14] states that the series of coaching for teachers is able to increase the ability of teachers so that they will develop in carrying out their teaching and learning activities. The encouragement obtained from academic supervision activities is a form of motivation.…”
Section: Hypothesis Testmentioning
confidence: 99%